Unveiling the Venom Composition of the Colombian Coral Snakes Micrurus Helleri, M. Medemi, and M. Sangilensis (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article is removed due to plagiarism The original work is available athttps://www.mdpi.com/2072-6651/15/11/622